2005
DOI: 10.1021/ja050447d
|View full text |Cite
|
Sign up to set email alerts
|

Indolactam-V Is Involved in the CH/π Interaction with Pro-11 of the PKCδ C1B Domain:  Application for the Structural Optimization of the PKCδ Ligand

Abstract: The CH/pi interaction between the indole ring of indolactam-V (IL-V) and the hydrogen atom at position 4 of Pro-11 of the PKCdelta C1B domain was evaluated using the mutant peptide of the PKCdelta C1B domain, in which the CH/pi interaction was inhibited by substitution of the hydrogen atom with a fluorine atom. IL-V showed about a 10 times lower binding affinity to the mutant peptide compared to the wild-type peptide, suggesting that the CH/pi interaction could play a pivotal role in the binding of IL-V to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 18 publications
0
38
0
Order By: Relevance
“…In addition, the lower Ki value of ILV (34) compared to compound 38 (80 and 1700 nM, respectively) was explained by CH/π interactions between the indole ring in ILV and Pro241 in PKCδ [135,140].…”
Section: Structure-activity Studiesmentioning
confidence: 94%
“…In addition, the lower Ki value of ILV (34) compared to compound 38 (80 and 1700 nM, respectively) was explained by CH/π interactions between the indole ring in ILV and Pro241 in PKCδ [135,140].…”
Section: Structure-activity Studiesmentioning
confidence: 94%
“…52 (−)-Indolactam V is a broad spectrum agonist of novel and classical PKCs. 54,55 But the novel PKC isoform Δ is a target of the RA-signaling pathway, providing evidence for an analogous effect of (−)-Indolactam V to that of RA on ESCs. 56,57 On the other hand, neither knock out of classical PKCs 58,59 nor knockout of novel PKCs 60,61 had a negative effect on mouse pancreatic, endocrine development as would be expected if PKC did play a critical role.…”
Section: Role Of Small Molecules During Differentiationmentioning
confidence: 99%
“…An instructive example underlying the importance of the CH··· interaction was reported by Irie and co-workers for the binding of indolactam-V (IL-V) and its analogs to the C1B domain of Protein kinase (PKC) C [44,45]. PKC isozymes are the main receptors of tumor promoters and mutational studies have revealed that Pro11 plays an important role in the binding of IL-V to PKC [46].…”
Section: Examples Of C ··· Interactions In Therapeutically Relevant Pmentioning
confidence: 99%